Criminal thinking, moral disengagement and psychological wellbeing in prisoners (Journal of Fatima Jinnah Medical University, 2019)
Background: Crime is the worldwide problem due to its increasing rate and diverse effects on the whole society.1 The current study sought to understand criminal behavior in Pakistani culture by exploring the relationship between criminal thinking, moral disengagement and psychological wellbeing in prisoners by taking psychological wellbeing as dependent variable.Subjects and methods: Correlational research design was used and the sample of adult prisoners was selected from District Jail Lahore by using purposive sampling technique. For assessment purpose demographic sheet, Criminal Thinking Scale, Moral Disengagement Scale, and Mental Health Continuum-Short Form were used. The data was stored and analyzed in SPSS version 20.Results: The results showed significant positive relationship between criminal thinking and moral disengagement whereas, significant negative correlation was found between criminal thinking and psychological wellbeing. Similarly moral disengagement was found to be negatively correlated with psychological wellbeing in prisoners. Regression analysis revealed that criminal thinking negatively predicts the psychological wellbeing. Moreover significant group differences on psychological wellbeing were found between convicted and under trial prisoners.Conclusion: The study concluded that criminal thinking, moral disengagement and psychological wellbeing are significantly correlated in crime context; therefore, various interventions for prediction of criminal attitude in various populations should be made by involving jail administration and the relevant policy makers.
Keywords: Criminal thinking; Moral disengagement; Psychological wellbeing; prisoners